Evaluation of Nexus Between Short-Run Return Measures of IPOs in India - Singh, Amit Kumar; Gill, Kawal; Kalra, Shivani (Indian Journal of Finance, 2023)
Purpose : This study aimed to provide a better understanding of the initial performance of initial public offerings (IPOs) on the day of listing by separating the gains on the listing day into primary and secondary market returns. An industry-wise evaluation of different return measures was done, and a year-on-year analysis was also conducted to understand more about the underpricing anomaly of IPOs. Methodology : The short-run IPO performance was analyzed using market-adjusted average returns (MAAR), focusing on the role of different factors in determining underpricing. The initial returns were divided into primary and secondary returns, and a sectoral analysis was conducted to evaluate the behavior of IPOs on the first day of trading. The quantitative analysis considered the returns from the issue date to the listing day opening price and compared the listing day opening and closing prices of all sample IPOs. Findings : The sectoral analysis revealed a reversal of the level of underpricing during the secondary market, which explains the listing day performance of IPOs under different industries over the last decade. According to the findings of this study, the subscription rate is a major determinant of short-run IPO performance. Practical Implications : To improve the short-run performance of IPOs, issuers should focus on increasing their subscription rates. This study recommended that corporations should publish credible, accurate, and adequate information and invite active participation from shareholders. Originality : Unlike prior research on IPOs, this study separated listing day gains into primary and secondary market returns, carried out an industry-wise evaluation of different return measures, and analyzed IPO behavior on the first day of trading to provide improved insights into the underpricing anomaly of IPOs.